Resistance of rose varieties to black spot - Myroshnychenko, D.; Pikovskyi, M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To evaluate the resistance of tea-hybrid and floribunda roses to black spot caused by the fungus Diplocarpon rosae F.A. Wolf. (Marssonina rosae (Lib.) Died.). Methods. Laboratory — for diagnosis of the disease and identification of its causative agent. Field — visual assessment of the distribution and degree of development of black spot (on a 6-point scale) on rose varieties under conditions of a natural infectious background. Mathematical and statistical — to assess the reliability of experimental results. Results. The conducted studies show that during the growing seasons of 2022—2023, black spotting was widespread on all varieties of hybrid tea roses. The intensity of disease development ranged from 30 to 70%. The average lesion score was 1.5—3.5. Ascot, Fiesta and Charming Piano varieties were noted to have the lowest degree of damage (30%). Among roses of the floribunda group, the spread of the disease was in the range of 25—100%, and its development was from 5 to 70%. The average damage score of different varieties was in the range of 0.25—3.5. The least amount of black spotting was seen on plants of the Blu fo Y variety. At the same time, its intensity of damage was 5%. There were no immune groups among rose varieties of two garden groups. Of the 12 varieties of tea-hybrid roses, highly resistant ones were also not found. 3 varieties were resistant, 6 were moderately resistant, and 3 were susceptible. Of the 11 floribunda rose varieties examined, one variety was characterized by high resistance, 3 were resistant, 5 were moderately resistant, and 2 were susceptible. Conclusions. According to the results of screening for resistance to black spot, 23 varieties of garden roses did not find immune roses among them. All studied varieties were affected by the causative agent of the disease D. rosae against a natural infectious background. Among the hybrid tea roses, Ascot, Fiesta and Charming Piano varieties are classified as resistant. The Blue Pho Yu variety (floribunda roses) was characterized by high resistance. Floribunda roses Sim Salabim, Bernstein and Four Elis were resistant to the disease. These varieties can be recommended for use in urban landscaping.